(3GdfRgI GdSfjI aj CNHGQ GdNdaGA hGdedhc GdeUQjIs - (3MSf Hf MSjf Hf CMeO, HOQ GdOjf GHf GdWhdhfj,J (B909 (3g` s
(3ChdgG (B:s
(3GdMeO ddg NGdb GdCee s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B189 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B217s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B39 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B275 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(3056) s
Keywords: (3GdJGQjNs